IMPROVED AND EXTREME GEOMETRO-KINEMATIC PARAMETERS OF HIGH-LOADED HYPERBOLOID GEARS - Nosko, Pavlo; Kashkarov, Sergii; Bashta, Oleksandr; Tsibriy, Yurii; Bashta, Alla (Problems of Friction and Wear, 2019)
Creation high-loaded hyperboloid gears with improved and extreme geometrykinematic parameters on the basis of quasi hyperboloid gearings – a perspective and effective direction in increase of technical and economic characteristics of reducers. Use of any reserves in manufacture hyperboloid gears and reducers can give and already really gives considerable economic benefit at the expense of improvement of a design, increase of labor productivity, improvement of quality, decrease in the cost price, increase of competitiveness of production.